CULTUREMAS DA GASTRONOMIA CEARENSE: MARCAS DE IDENTIDADE LINGUÍSTICA E CULTURAL | CULTUREMS OF CEARENSE GASTRONOMY: LANGUAGES OF LANGUAGE AND CULTURAL IDENTITY - Costa, Expedito Wellington Chaves; Marçalo, Maria João (Estudos Linguísticos e Literários, 2019)
Resumo: Atualmente a língua é uma instituição social diversificada entre grupos e varia ao longo do tempo, sofrendo mudanças ou conservando características de períodos históricos. Deseja-se demonstrar que os culturemas da gastronomia cearense contribuem para a formação da identidade linguística e cutural do povo do Ceará. Para fundamentação, recorre-se, entre outros, a Pamies Bertrán (2012), Biderman (1978), e Luque Nadal (2009). Aqui, a gastronomia é inserida no âmbito da cultura imaterial por representar a tradição histórica e cultural de um povo. Metodologicamente, catalogam-se culturemas da gastronomia cearesense que se desdobram em expressões idiomáticas características do dialeto cearense. Resultados comprovam a influência dos culturemas na identidade linguística do cearense. Abstract: Today language is a social institution diversified between groups and varies over time, undergoing changes or retaining characteristics of historical periods. It is desired to demonstrate that the Ceará gastronomic culturemas contribute to the formation of the linguistic and cutural identity of the people of Ceará. For reasons of support, we refer to, among others, Pamies Bertrán (2012), Biderman (1978), and Luque Nadal (2009). Here, gastronomy is inserted in the scope of intangible culture because it represents the historical and cultural tradition of a people. Methodologically, we catalog the cul- tures of the Cearense gastronomy that unfold in idiomatic expressions characteristic of the Ceará dialect. Results prove the influence of culturemas on the linguistic identity of Ceará. Keywords: Culturemas; Gastronomy; Identity; Dialect.